A New Five Parameter Lifetime Distribution: Properties and Application - Dessoky, Shimaa A.; Abd El-Bar, Ahmed M. T. (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
This paper deals with a new generalization of the Weibull distribution. This distribution is called exponentiated exponentiated exponential-Weibull (EEE-W) distribution. Various structural properties of the new probabilistic model are considered, such as hazard rate function, moments, moment generating function, quantile function, skewness, kurtosis, Shannon entropy and Rényi entropy. The maximum likelihood estimates of its unknown parameters are obtained. Finally, areal data set is analyzed and it observed that the present distribution can provide a better fit than some other known distributions.